Approach to Patients with Chylothorax Complicating Pulmonary Resection - Akin, H.; Olcmen, A.; Isgorucu, O.; Denizkiran, I.; Dincer, I. (The Thoracic and Cardiovascular Surgeon, 2012)
Mediastinal lymph node dissection, an important part of surgery for non-small cell lung cancer, is associated with a risk of chylothorax. Although mortality has significantly decreased in recent years, it still worries thoracic surgeons. In this report we reviewed our experience on chylothorax with 26 cases and assessed the outcomes after conservative and surgical approaches. Between January 2000 and June 2010, twenty-six patients developed chylothorax after pulmonary resection performed for non-small cell lung cancer. Initially, all cases were treated conservatively with cessation of oral intake and the application of talc poudrage. If the conservative method failed, a surgical approach was used, which consisted either of suturing the leak or of mass ligation. The mean age of patients was 56 ± 9.05 years, and 3 were female. Chylothorax was more common on the right side, in lobectomy cases, in cases with adenocarcinoma, and in patients with advanced stage lung cancer, but the difference did not reach statistical significance. Conservative treatment was successful in 19 of 26 (73 %) patients, four of whom had undergone pneumonectomy. Seven out of 26 cases (27%) required thoracotomy to control the chylous leak. Though thoracotomy was required mostly for the right side (6 right vs. 1 left, p = 0.15), and in patients who had had pneumonectomy as their first operation (4 patients vs. 3, p = 0.18), this did not reach statistical significance. No patient died as a result of surgical intervention. In conclusion, chylothorax is not rare after pulmonary resection performed for lung cancer. But it is not as dangerous as it used to be. Talc pleurodesis has increased the success of conservative management and minimized the need for surgical intervention. In cases of high output leak the surgeon should not hesitate to perform surgery. VATS can be performed instead of open surgery in suitable cases.
Keywords: lung cancer treatment (surgery medical); thoracic duct; surgery; complications